Phenomenon of macrophyte differentiation in a small lake - Sender, Joanna; Danuta, Urban; Różańska-Boczula, Monika (Penerbit Universiti Kebangsaan Malaysia, 2020)
The main objective of the research was to determine the causes of qualitative and quantitative variability of macrophytes within the lake. The study involved the analysis on factors warning their diversity, and also to understand if these factors were inside or outside the lake. In addition, attempts were made to indicate which group of macrophytes showing the strongest response to these factors. The determination of such factors will permit taking protective measures regarding the lake. Lake Głębokie Uścimowskie is located in the western part of the Łęczna-Włodawa Lake District (Poland). It is an eutrophic water body with a surface area of 20.5 ha and maximum depth 7.1 m. Lake Głębokie Uścimowskie is a small and shallow lake constituting a diverse habitat for macrophytes. The littoral slope, buffer zone slope, and buffer zone land use had the greatest impact on the macrophyte diversity of the lake. An increase in the value of these variables affected features such as helophyte biomass, helophyte range, and depth of macrophyte occurrence to the greatest degree. Wind direction, which influenced the number of nympheid species, was also highly correlated. The Secchi disc visibility variable had the strongest influence on submerged macrophytes. As a rule, in the studied lake, if the rushes zone was developed, the development of submerged macrophytes was limited. Poorly developed rushes were accompanied by greater variability among submerged macrophytes.